Therapeutic inhibition of keratinocyte TRPV3 sensory channel by local anesthetic dyclonine - Qiang Liu; Jin Wang; Xin Wei; Juan Hu; Conghui Ping; Yue Gao; Chang Xie; Peiyu Wang; Peng Cao; Zhengyu Cao; Ye Yu; Dongdong Li; et al. (eLife, 2021)
The multimodal sensory channel transient receptor potential vanilloid-3 (TRPV3) is expressed in epidermal keratinocytes and implicated in chronic pruritus, allergy, and inflammation-related skin disorders. Gain-of-function mutations of TRPV3 cause hair growth disorders in mice and Olmsted syndrome in humans. Nevertheless, whether and how TRPV3 could be therapeutically targeted remains to be elucidated. We here report that mouse and human TRPV3 channel is targeted by the clinical medication dyclonine that exerts a potent inhibitory effect. Accordingly, dyclonine rescued cell death caused by gain-of-function TRPV3 mutations and suppressed pruritus symptoms in vivo in mouse model. At the single-channel level, dyclonine inhibited TRPV3 open probability but not the unitary conductance. By molecular simulations and mutagenesis, we further uncovered key residues in TRPV3 pore region that could toggle the inhibitory efficiency of dyclonine. The functional and mechanistic insights obtained on dyclonine-TRPV3 interaction will help to conceive therapeutics for skin inflammation.